The growth dynamics of Douglas fir in Sweden and Finland - Nemec, Wolfgang (2014)
Little research has yet been conducted on the growth of Douglas fir (Pseudotsuga menziesii (Mirbel) Franco var. menziesii) in Sweden albeit its potentials as a commercial tree species in the future. Therefore, this study aimed at capturing currently available field and reference data for the purpose of evaluation. Another objective of this study was to predict the growth dynamics of Douglas fir in Sweden and Finland using the 3-PG stand growth model presented by Landsberg & Waring (2003). In order to test the validity of the simulated outcomes, the predictions were tested against the available field data. The findings showed that already in 1961, Karlberg (1961) made the attempt to gather available information on the growth of Douglas fir and created yield tables for height, DBH and volume development with the data he had found. Despite his extensive data collection from 187 field plots in southern Sweden and Denmark, there was a significant disagreement of volume increment compared to more recent measurements by SLU. The few available research plots managed by SLU indicate a low volume increment in the early years of the stand but pick up a fast growth rate at a later stand age. The Karlberg data (Karlberg, 1961) on the other hand, tends to increase strongly in the first 50 years but then levels out. The 3-PG stand growth model performed reasonably well for height and DBH predictions in comparison to the field data. Yet again, volume predictions were less successful to match the field data curves. A model validation calculating the mean average deviation (MAD) of the predicted from the field data showed a deviation from height in the range of 5.7 and 23%, from DBH in the range of 1.7 and 24.8%, and from volume between 25.5 and 103.4%, using 3-PG Version 1.0 or 2.7 and either a fertility rating of 0.5 or 0.8, respectively. The outcomes demonstrate that the application of the 3-PG stand growth model for simulating growth of an exotic tree species in Scandinavia is feasible with limitations. Special care should be laid on the calibration of species- and site-specific parameters.